Factors of adaptative performance in teachers of the Universidad Autónoma de Tamaulipas, in the post-COVID-19 stage - González Solís, Astrid; Delgado Rivas, Jesús Gerardo; Mendoza Flores, José Esteban (IE Revista de Investigación Educativa de la REDIECH, 2025)
When facing the COVID-19 pandemic, universities in Mexico carried out different strategies to continue teaching their classes in a distant way, closing their face-to-face class facilities. The new post-COVID-19 scenario in university life has led to the development of research on teachers and students to measure the impact of the pandemic on academic life. This study emphasizes the teachers and their ability to adapt the work activities because of the needs that this epidemiological phenomenon demanded, for this reason, it aims to identify the adaptive performance determinants taking as an analysis unit the professors from the Facultad de Derecho y Ciencias Sociales Victoria of the Universidad Autónoma de Tamaulipas, in which a quantitative study with an exploratory scope was carried out.